Analysis of maximum air temperature distribution - Jokimaitis, Arvydas; Petronaitis, Darius (Lietuvos matematikos rinkinys, 2015)
The article authors detected distribution estimates of maximum air temperature. Also estimated ultimate temperature record and found quality of temperature record.